Case report: novel NFKB2 variant associated with pediatric eosinophilic granulomatosis with polyangiitis (EGPA) in the COVID-19 pandemic - Li Lin; Xin Peng; Lina Chen; Liqun Dong; Lin Zhong (Pediatric Rheumatology Online Journal)
Abstract Background Childhood-onset eosinophilic granulomatosis with polyangiitis (cEGPA) is a rare type of systemic autoimmune disorder. Variants in the NFKB2 gene can manifest as common variable immunodeficiency or combined immunodeficiency, often accompanied by autoimmunity and ectodermal dysplasia. Here, we report a case of a Chinese patient who carries NFKB2 variants that coexist with cEGPA, a novel combination which, to our knowledge, has not been previously published. Case presentation We reported a 9-year and 10-month-old girl who presented with cough, wheezing, dyspnea, hypereosinophilia, and vasculitis. Notably, she had significant bilateral pulmonary interstitial lesions. We performed metagenomic next-generation sequencing (mNGS), bronchoscopy and immunological analysis. She was considered to have refractory cEGPA after six months of corticosteroid and immunosuppressive treatment. Tapering off corticosteroids posed a challenge, and multiple immunosuppressive agents were ineffective. Our patient suffered from recurrent fever, wheezing, dyspnea and perianal abscess, along with life-threatening infections, including pneumocystis jirovecii pneumonia (PJP) and severe coronavirus disease 2019 (COVID-19) pneumonia during the pandemic. Her cytokines and inflammatory markers showed a profound collapse. She developed significant hypoxemia, which necessitated mechanical ventilation. Primary immunodeficiency gene panel testing revealed a novel de novo variant in NFKB2 (c.2578 + 2 dup) that was classified as pathogenic. Despite treatment with antibacterial, antiviral, and antifungal agents, biologics, and plasma exchange, she ultimately succumbed to respiratory failure. Conclusions This case report establishes a novel link between NFKB2 variants and EGPA, particularly in the context of the COVID-19 pandemic. This study expands the spectrum of NFKB2 variants and vividly illustrates the complex interrelationships among autoimmunity, infection, and immunodeficiency.